1991
DOI: 10.1111/j.1440-1819.1991.tb02487.x
|View full text |Cite
|
Sign up to set email alerts
|

Monotherapy for Childhood Epilepsies with Zonisamide

Abstract: Zonisamide was tried on 44 children, 18 girls and 26 boys, from 8 months to 15 years of age at the start of the trial. In 6 children the drug has been stopped because of side effects. The drug was introduced at a dose of 2-4 mg/kg/day and increased to 12 mg/kg/day unless a satisfactory response occurred at a Power dose. A 1OOyo control of seizures was achieved in 5 of 5 cases of idiopathic generalized epilepsies, in 7 of 8 cases of symptomatic generalized epilepsies, in one of one case of idiopathic partial ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…ZNS was started at 2 4 mg/ kg/day and increased until toxicity or satisfactory response occurred, with the maximal dose being 12 mg/ kg/day. In five cases of idiopathic generalized epilepsy, all achieved control, and in 7/8 cases of symptomatic generalized epilepsy, control was achieved (43).…”
Section: Efficacy In Generalized Epilepsiesmentioning
confidence: 93%
See 1 more Smart Citation
“…ZNS was started at 2 4 mg/ kg/day and increased until toxicity or satisfactory response occurred, with the maximal dose being 12 mg/ kg/day. In five cases of idiopathic generalized epilepsy, all achieved control, and in 7/8 cases of symptomatic generalized epilepsy, control was achieved (43).…”
Section: Efficacy In Generalized Epilepsiesmentioning
confidence: 93%
“…In a study of children, 17 of 24 cases of symptomatic partial epilepsy had complete remission of seizures (43).…”
Section: Efficacy In Localization-related Epilepsiesmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][42][43][44][45][46] For the purposes of this review, the responder rate was defined as the percentage of patients whose seizure frequency dropped by 50% or greater (compared with baseline) during zonisamide treatment. The remaining 2 trials40,41 did not present summary responder rates for partial-or generalized-onset seizures but, rather, responder rates for individual seizure subtypes.…”
Section: Metabolism and Excretionmentioning
confidence: 99%
“…Recently, Velizarova et al 11 have also reported that refractory juvenile absence epilepsy can be controlled with ZNS, but nearly 30% (4 of 13) of their patients need high doses (>500 mg/d). In a monotherapy trial including 44 pediatric patients (25 with localization-related epilepsy and 13 with generalized epilepsy) reported by Kumagai et al, 12 ZNS was used in doses of up to 12 mg/kg per day (again considered high doses, the recommended dose in children being 8 mg/kg per day). Seizure freedom was achieved in 72% of subjects with localizationrelated epilepsy (18 of 25) and in 91% of those with generalized epilepsy (12 of 13).…”
Section: Discussionmentioning
confidence: 99%